Zdravljenje spastičnosti - z dokazi podprta medicina - Grabljevec, Klemen (Rehabilitacija (Ljubljana), 2010)
Systematic search of PUBMED and MEDLINE was carried out on studies performed in the field of focal and generalysed spasticity treatment. The described studies involve the use of casting, botulinum toxin and intrathecal baclofen. Due to small samples, most studies have low quality of evidence and weak level of recommendations.
Keywords: botulin toksin; intratekalni baklofen; neurology; nevrologija; spastičnost; therapy; zdravljenje